Evaluation of the Life Cycle of Aedes albopictus and Its Control Strategy Using Deltamethrin and Lambda-Cyhalothrin as Larvicides (Bioresearch Communications, 2025)
Dengue fever, transmitted by Aedes aegypti and Aedes albopictus, has seen a global increase, with A. albopictus particularly prevalent in Dhaka, Bangladesh, during the study period, August 2023 to July 2024. This study focused on controlling dengue at the vector level, specifically targeting A. albopictus, which was identified in both larval and adult stages through morphological analysis. Results showed that A. albopictus larvae took about three times longer to develop into adults during winter than in summer. The effectiveness of two pyrethroid insecticides, lambda-cyhalothrin and deltamethrin, was assessed by determining lethal concentrations (LC50 and LC90), emergence inhibition (IE50 and IE90), and resistance ratios (RR) for late 3rd and early 4th instar larvae. Current LC50 and LC90 values for lambda-cyhalothrin were 0.29 ppm and 0.47 ppm, while deltamethrin values were 0.24 ppm and 0.69 ppm, showing a significant rise from previous levels and indicating increased resistance (p